Strategy Formulation to Optimize Revenue of Medical Devices Company - Saragih, Yan Irwan Antoni (Journal of Sustainable Community Development (JSCD), 2024)
The government of Indonesia is implementing a transition in the sustainability of the health system that includes, among other things, the development of medical devices made in the country to reduce its reliance to imported medical devices. Through The Regulation of The President of Republic of Indonesia Number 12 of 2021, the ministries/institutions/regional apparatuses are obligated to use domestic products, including national design and engineering. The obligation to use domestic products is performed if there are domestic products that have the sum of National Contribution Value (Tingkat Komponen Dalam Negeri, TKDN) plus the Corporate Contribution Value (Bobot Manfaat Perusahaan, BMP) of a minimum of 40% (forty percent). The change of new regulation impacted PT XYZ, a company supplying medical devices mostly to government institution experienced turbulence, sales performance 2022 drop more than 50% compared with 2021. New business strategy is needed to adapt, develop distinctive value to set apart from rivals and at the end optimize the revenue. The study uses of a thorough research technique performed in June – October 2024 that comprises business model canvas, stakeholder analysis, TOWS matrix, Porter's Five Forces Analysis, VRIO Analysis.